Stimulasi Motorik Halus melalui Kegiatan Art Therapy Meronce Bagi ABK di SLB C Perwari Kuningan - Fadia Miralda; Farid Ridwan; Fathimah Azzahra Hafis (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service project aims to enhance the fine motor skills of children with special needs (CWSN) at SLB C YPALB Perwari Kuningan through a beading-based art therapy approach. The program was conducted using a participatory and enjoyable educational method. A descriptive qualitative method was employed, with data collected through direct observation, informal interviews, and documentation of students' creative outputs. The results showed a significant improvement in hand-eye coordination, concentration, and perseverance among the participants. Children with intellectual disabilities, hearing impairments, autism, and Down syndrome successfully created rings and bracelets, both independently and with guidance. This activity not only contributed to fine motor development but also enhanced social interaction and self-expression. With its inclusive and adaptive approach, beading as a form of art therapy proved effective in supporting the learning process and holistic development of children with special needs in special education settings.